A case of combination of Eales disease and Arnold Chiari syndrome (Ukrainian Journal of Ophthalmology, 2026)
Purpose. A description of a rare combination of Arnold — Kiari syndrome and Eales Disease is given. Material and Methods. We followed up a 24 y.o. patient with Eales Disease combined with Arnold — Kiari syndrome.Results. According to clinical and functional examination data, a patient was diagnosed Ealse disease. Taking into account changes in the optic disc which are not typical for that disease, a patient was performed MRT of the head which revealed the presence of Arnold — Kiari syndrome.Conclusion. The present clinical case is evidence of combination of Arnold — Kiari syndrome and Eales Disease, thus, practical ophthalmologist should have that in mind and examine patients carefully.
Keywords: Eales Disease; Arnold — Kiari syndrome; diagnostics